Multi-omics analysis identifies TLRscore for prognostic prediction and highlights TLR8 in macrophage-mediated antitumor immunity of lung adenocarcinoma - Li, Ang; Liu, Jiawei; Wu, Hongjiao; Jin, Ye; Zhang, Hongmei; Zhang, Zhi; Jiang, Shunli; Zhang, Xuemei (Frontiers in Immunology, 2026)
BackgroundToll-like receptors (TLRs) are key mediators of innate and adaptive immunity. Understanding their role in tumor immunity is essential for improving checkpoint blockade therapies.MethodsUsing TCGA data from 32 cancers, we assessed TLR expression, prognosis, and epigenetic changes. A TLRscore was constructed with ssGSEA to evaluate associations with immune infiltration, survival, drug sensitivity, and immunotherapy outcomes, validated in lung adenocarcinoma (LUAD) cohorts. TLR8 polymorphism was genotyped by PCR-RFLP, and the rs3761624 variant was functionally analyzed by luciferase assay. Functional assays in LUAD cells and macrophages treated with the TLR8 agonist Motolimod examined proliferation, migration, invasion, phagocytosis, mitochondrial activity, and ROS generation.ResultsTLRs showed altered expression, frequent mutations, copy number variations, and methylation regulation in cancer. High TLRscore predicted favorable prognosis, increased immune infiltration, and improved immunotherapy response in LUAD. TLR8 was the most immunologically relevant, strongly linked to macrophage infiltration, PD-L1 expression, and T-cell activity. The rs3761624 SNP suppressed TLR8 transcription via enhanced NR1D1 repression. Motolimod reprogrammed macrophages toward an M1 phenotype, boosting cytokine secretion, phagocytosis, and antitumor activity, while inhibiting LUAD cell growth. Mechanistically, TLR8 activation in macrophages was associated with reduced mitochondrial membrane potential, increased ROS production, and the acquisition of an M1-like, antitumor phenotype with enhanced phagocytosis and cytokine secretion.ConclusionTLRscore is a novel biomarker for prognosis and immunotherapy response, while TLR8 represents a promising therapeutic target in LUAD, providing mechanistic insight into potential combination strategies.